2018
DOI: 10.15694/mep.2018.0000061.1
|View full text |Cite
|
Sign up to set email alerts
|

Study Habits of Medical Students: An Analysis of which Study Habits Most Contribute to Success in the Preclinical Years

Abstract: Academic performance during the first two years of medical school is an important predictor of success on the United States Medical Licensing Exam Step 1. Research is lacking into what study methods successful students use, with success being defined as achieving a grade point average of above 90% in all or in most of the courses in the preclinical years.This study sought to identify specific study habits that successful students use and to demonstrate an association between preclinical grades and Step 1 score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
2
19
0
2
Order By: Relevance
“…Engaging with the lecture recording as described above is one way to support these revision session. If the live lecture was attended it seems to be an ineffective strategy to simply re-watch the recording (Liles et al, 2018). A spaced approach to learning, i.e.…”
Section: Identify Problem Areas and Watch Specific Sections Of A Recomentioning
confidence: 99%
“…Engaging with the lecture recording as described above is one way to support these revision session. If the live lecture was attended it seems to be an ineffective strategy to simply re-watch the recording (Liles et al, 2018). A spaced approach to learning, i.e.…”
Section: Identify Problem Areas and Watch Specific Sections Of A Recomentioning
confidence: 99%
“…The relatively lackluster effects of rereading just for the sake of reading also arise when students rewatch video‐recorded lectures. Liles et al () recently reported that many medical students who received “C” grades reported rewatching online lectures as a learning strategy, whereas those who received “A” grades almost never reported rewatching lectures. These data corroborate the observations that rereading and rewatching lectures are ineffective learning strategies.…”
Section: Blueprint To Learningmentioning
confidence: 99%
“…Deciding on powerful techniques to study in medical school is of utmost significance. 17 Subsequently, a comprehension of the kinds of study habits that are best in medical school is imperative, as the early realization of the study habits that are associated with progress can assist students in reaching their maximum capability and accomplishing proficiency during the pre-clinical and clinical years, which will help them in the residency selection program. 18,19 One of the core academic aims has always been the enhancement of student success.…”
Section: Introductionmentioning
confidence: 99%